CO2-mediated thermocatalytic monomer recovery from decomposable drinking straw waste over a tricalcium phosphate catalyst - Lee, Seonho; You, Tak Hyun; Cho, In Sun; Lee, Jechan (Chemical Engineering Journal, 2023)
Proper treatment of decomposable plastic waste and plastic waste upcycling for value-added chemical recovery have increasing attention in recent years. Tricalcium phosphate (TCP; Ca3P2O8) is one of the most studied biomaterials for bone replacement and regeneration. Herein, we endeavored to apply the TCP catalyst to a thermocatalytic conversion process of decomposable polylactic acid (PLA) straw waste (PLASW) in order to recover value-added monomer (e.g., lactic acid). The TCP catalyst was synthesized using a solid-state reaction method, showing micron-sized particles with small fragments (50–300 nm). The thermocatalytic PLASW conversion was tested under different atmospheric conditions (N2 versus CO2) with and without the TCP catalyst. The TCP catalyst noticeably enhanced the lactic acid recovery yield under both the N2 and CO2 environments compared with non-catalytic PLASW conversion. The highest lactic acid recovery yield (15.2 wt% of the feedstock) was achieved on the TCP catalyst under the CO2 environment, which was about 3 times higher than the non-catalytic PLASW conversion. The enhancement of lactic acid recovery was due to the base sites present on the TCP catalyst promoting hydrogen transfer reaction for selective PLA bond cleavage. Less coke formation on the TCP catalyst was also observed under the CO2 environment than under the N2 environment. The results show that TCP has the potential as a catalyst used for recovering value-added chemicals from bioplastic waste via a thermocatalytic upcycling process.
Keywords: Bio-plastics; Lactic acid recovery; Non-catalytic; Plastics waste; Recovery yield; Thermo chemical process; Tri-calcium phosphates; Value-added chemicals; Waste conversion; ]+ catalyst; Bioplastic; Plastic waste; Thermochemical process; Tricalcium phosphate; Waste management